Met receptor signaling is required for sensory nerve development and HGF promotes axonal growth and survival of sensory neurons - Maina, Flavio (Cold Spring Harbor Laboratory Press, 1997)
The development of the nervous system is a dynamic process during which factors act in an instructive fashion to direct the differentiation and survival of neurons, and to induce axonal outgrowth, guidance to, and terminal branching within the target tissue. Here we report that mice expressing signaling mutants of the hepatocyte growth factor (HGF) receptor, the Met tyrosine kinase, show a striking reduction of sensory nerves innervating the skin of the limbs and thorax, implicating the HGF/Met system in sensory neuron development. Using in vitro assays, we find that HGF cooperates with nerve growth factor (NGF) to enhance axonal outgrowth from cultured dorsal root ganglion (DRG) neurons. HGF also enhances the neurotrophic activities of NGF in vitro, and Met receptor signaling is required for the survival of a proportion of DRG neurons in vivo. This synergism is specific for NGF but not for the related neurotrophins BDNF and NT3. By using a mild signaling mutant of Met, we have demonstrated previously that Met requires signaling via the adapter molecule Grb2 to induce proliferation of myoblasts. In contrast, the actions of HGF on sensory neurons are mediated by Met effectors distinct from Grb2. Our findings demonstrate a requirement for Met signaling in neurons during development.